Pureed Foods: Lentil Desserts - Wendy J Dahl; Alison O'Donoughue (EDIS, 2018)
A pureed diet may be recommended for individuals with swallowing problems; however, it can be challenging for those with a puréed diet to receive adequate protein, fiber, vitamins, and minerals. This 4-page document provides recipes made with puréed lentils, offering desserts that are both tasty and nutrient-dense. Written by Wendy J. Dahl and Alison O’Donoughue and published by the UF/IFAS Department of Food Science and Human Nutrition, March 2018. http://edis.ifas.ufl.edu/fs306